Combined experimental and theoretical study on the removal of pollutant compounds by peroxidases: affinity and reactivity toward a bioremediation catalyst - Silva, Maria Cristina; Torres, Juliana Arriel; Castro, Alexandre A; da Cunha, Elaine F F; Alves de Oliveira, Luiz Carlos; Corrêa, Angelita Duarte; Ramalho, Teodorico C (Journal of biomolecular structure & dynamics, 2016)
Water pollution is a significant and growing problem throughout the world, especially in developing countries. In order to minimize environmental problems, catalysts have increasingly been designed to remove pollutants from the water. In an attempt to innovate by the creation of new low-cost alternatives to efficiently remove pollutants, the enzymatic treatment has been intensely studied for this purpose. Reactions catalyzed by enzymes are able to perform specific treatments, commonly with high rates of the final products. With this, the enzyme, peroxidase, is a promising candidate as a bioremediation catalyst. The efficiency of oxidoreductive enzymes, such as horseradish peroxidase (HRP) and soybean peroxidase (SP) have been studied, given that their performance depends on the substrate. In this investigation, experimental techniques and theoretical calculations have been employed in order to investigate the oxidative process for the ferulic acid and bromophenol blue dyes, performed by HRP and SP. Both enzymes showed a comparable behavior with respect to ferulic acid substrate. On the other hand, by utilizing bromophenol blue dye as a substrate, the behavior of the employed catalysts was significantly different. Experimental data have shown that HRP was more active toward bromophenol blue when compared to ferulic acid, being more rapidly degraded by the HRP enzyme. This tendency was confirmed by our theoretical docking, PM6 semi-empirical method, and DFT calculation results, in which the interaction, binding energies, and transition states were determined.
Keywords: soybean peroxidase; Catalysis; molekulární konformace; vodíková vazba; Kinetics; teoretické modely; Peroxidases; biodegradace; bromfenolová modř; Molecular Docking Simulation; vazebná místa; katalýza; Substrate Specificity; simulace molekulového dockingu; Bromphenol Blue; vazba proteinů; pollutant; peroxidasy; Coumaric Acids; Molecular Conformation; Models, Molecular; oxidace-redukce; experimental techniques; molekulární modely; katalytická doména; Oxidation-Reduction; Environmental Pollutants; HRP; theoretical calculations; Hydrogen Bonding; Biodegradation, Environmental; kyseliny kumarové; látky znečišťující životní prostředí; substrátová specifita; Models, Theoretical; Protein Binding; kinetika; Catalytic Domain; Binding Sites